Optimal forwarding policy in opportunistic based on social features of nodes - Zhi-fei WANG; Pei-teng SHI; Su DENG; Hong-bin HUANG; Ya-hui WU (Tongxin xuebao)
A forwarding model of opportunistic network was established based on social features of node and by introducing the Pontryagin’s maximal principle,the optimal policy was got,which obeyed the threshold form.Let h denotes the stop time,when t＆lt;h,nodes forward the messages with the maximum probability,when t＆gt;h,the node stops sending messages.Experiments show that the optimal strategy is better than optimal static policy.Further analysis show that the bigger the average number of friends of node is,the smaller the stopping time is,the better the performance is.